Multiple rearrangements and low inter- and intra-species mitogenome sequence variation in the Heterobasidion annosum s.l. species complex - Himmelstrand, Kajsa; Brandström Durling, Mikael; Karlsson, Magnus; Stenlid, Jan; Olson, Åke (Frontiers in Microbiology, 2023)
Introduction Mitochondria are essential organelles in the eukaryotic cells and responsible for the energy production but are also involved in many other functions including virulence of some fungal species. Although the evolution of fungal mitogenomes have been studied at some taxonomic levels there are still many things to be learned from studies of closely related species. Methods In this study, we have analyzed 60 mitogenomes in the five species of the Heterobasidion annosum sensu lato complex that all are necrotrophic pathogens on conifers. Results and Discussion Compared to other fungal genera the genomic and genetic variation between and within species in the complex was low except for multiple rearrangements. Several translocations of large blocks with core genes have occurred between the five species and rearrangements were frequent in intergenic areas. Mitogenome lengths ranged between 108 878 to 116 176 bp, mostly as a result of intron variation. There was a high degree of homology of introns, homing endonuclease genes, and intergenic ORFs among the five Heterobasidion species. Three intergenic ORFs with unknown function (uORF6, uORF8 and uORF9) were found in all five species and was located in conserved synteny blocks. A 13 bp long GC-containing self-complementary palindrome was discovered in many places in the five species that were optional in presence/absence. The within species variation is very low, among 48 H. parviporum mitogenomes, there was only one single intron exchange, and SNP frequency was 0.28% and indel frequency 0.043%. The overall low variation in the Heterobasidion annosum sensu lato complex suggests a slow evolution of the mitogenome.